Board of Director Characteristics, Institutional Ownership, and Accounting Conservatism - Ni Wayan Rustiarini; Agus Wahyudi Salasa Gama; Desak Nyoman Sri Werastuti (The Indonesian Journal of Accounting Research, 2021)
One of the determinants of conservatism is the characteristics of the board of directors. Several studies have examined the relationship between board characteristics and accounting conservatism. Nonetheless, previous empirical findings show heterogeneous and inconclusive results. This study aims to prove the role of board characteristics, namely board size, board female, and board overconfidence, in accounting conservatism. This study also explores the role of institutional ownership in moderating the board characteristic relationship and accounting conservatism. This research was conducted on 123 manufacturing companies for three observation periods, namely 2017-2019. The sampling method used purposive sampling. The data analysis technique used is Partial Least Square. The test results prove that board size and board female increase accounting conservatism, while board overconfidence reduces conservatism. The study results also indicate that institutional ownership can strengthen the relationship between board size and board female to accounting conservatism. Contrary, institutional ownership failed to moderate the relationship between board overconfidence and accounting conservatism.